Cellular Delivery and Photochemical Activation of Antisense Agents through a Nucleobase Caging Strategy - Govan, Jeane M. (2013)
Antisense oligonucleotides are powerful tools to regulate gene expression in cells and model organisms. However, a transfection or microinjection is needed for efficient delivery of the antisense agent. We report the conjugation of multiple HIV TAT peptides to a hairpin-protected antisense agent through a light-cleavable nucleobase caging group. This conjugation allows for the facile delivery of the antisense agent without a transfection reagent and photochemical activation offers precise control over gene expression. The developed approach is highly modular, as demonstrated by the conjugation of folic acid to the caged antisense agent. This enabled targeted cell delivery through cell-surface folate receptors followed by photochemical triggering of antisense activity. Importantly, the presented strategy delivers native oligonucleotides after light-activation, devoid of any delivery functionalities or modifications that could otherwise impair their antisense activity.